2019
DOI: 10.1088/1742-6596/1280/3/032018
|View full text |Cite
|
Sign up to set email alerts
|

First-year university students’ understanding of chemical equilibrium

Abstract: This study analyzed the understanding of first-year students on the concept of chemical equilibrium. It involved 30 first-year students in the faculty of mathematics and natural sciences of Universitas Negeri Padang. The students’ understanding was explored using a conceptual test. The result shows that generally, students have misconceptions about the concept of chemical equilibrium especially when the reaction reaches equilibrium as reported by many studies. The results of this study have implications for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…For example, prior to the implementation of this activity, it is important that instructors introduce students to the idea of multistep equilibria. Research on students’ ideas about chemistry equilibrium has shown that students believe that (1) the forward and reverse reactions alternate and are distinct events and (2) equilibrium reactions go to completion before the reverse reaction begins. By introducing students to these types of multistep reactions, we could potentially reduce the level of complexity associated with multistep equilibrium reactions and focus on the dynamic and reversible nature of the reaction being presented.…”
Section: Student Work and Discussionmentioning
confidence: 99%
“…For example, prior to the implementation of this activity, it is important that instructors introduce students to the idea of multistep equilibria. Research on students’ ideas about chemistry equilibrium has shown that students believe that (1) the forward and reverse reactions alternate and are distinct events and (2) equilibrium reactions go to completion before the reverse reaction begins. By introducing students to these types of multistep reactions, we could potentially reduce the level of complexity associated with multistep equilibrium reactions and focus on the dynamic and reversible nature of the reaction being presented.…”
Section: Student Work and Discussionmentioning
confidence: 99%
“…A temática equilíbrio químico, no contexto da sala de aula apresenta uma elevada riqueza conceitual como consequência da articulação com diferentes conceitos químicos, dos quais podemos citar: reações químicas, estequiometria, reversibilidade reacional, noções cinéticas e termodinâmicas (SILVA; AMARAL, 2017;AINI et al, 2018;SATRIANA et al, 2018;MATEUS;FERREIRA, 2021). Somado a isso, a aplicação dos princípios do conceito também é diversificada, podendo ou não estar relacionada à aspectos mais próximos do cotidiano do sujeito.…”
Section: Introductionunclassified
“…São eles: I) a associação de equilíbrio a um estado estático; II) a concentração de reagentes e produtos iguais; III) sistema como um processo reversível, mas não simultâneo; IV) a compartimentalização do sistema; e, por fim, V) a aplicação automática e indiscriminada do princípio de Le Chatelier (AINI et al, 2018;JÚNIOR;SILVA, 2009;ANDRADE;IZAIAS, 2016;VETERE;CAPPANNINI;ESPÍNDOLA, 2017). Parece ser consensual que tais concepções alternativas são derivadas das experiências cotidianas dos discentes relacionada à ideia geral de equilíbrio, que tendem a estar associada às ideias de estabilidade, igualdade e estaticidade (balança, equilibrar em cordas etc.…”
unclassified